Amphiphilic chitosan-grafted-functionalized polylactic acid based nanoparticles as a delivery system for doxorubicin and temozolomide co-therapy - Di Martino, Antonio; Sedlarik, Vladimir (International journal of pharmaceutics, 2014)
The aim of this work was to investigate the potential of an amphiphilic system comprising chitosan-grafted polylactide and carboxyl-functionalized polylactide acid as a carrier for the controlled release and co-release of two DNA alkylating drugs: doxorubicin and temozolomide. Polylactide and carboxyl-functionalized polylactide acid were obtained through direct melt polycondensation reaction, using methanesulfonic acid as a non-toxic initiator, and subsequently these were grafted to the chitosan backbone through a coupling reaction, utilizing 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide as a condensing agent. ATR-FTIR analysis and conductometric titration confirmed that a reaction between CS and PLA, PLACA2% and PLACA5% occurred. Chitosan-grafted-polylactide and polylactide-citric acid nanoparticles were prepared via the polyelectrolyte complex technique, applying dextran sulphate as a polyanion, and loaded with doxorubicin and temozolomide. The diameter of particles, ζ-potential and their relationship to temperature and pH were analysed in all formulations. Encapsulation, co-encapsulation efficiency and release studies were conducted in different physiological simulated environments and human serum. Results showed the continuous release of drugs without an initial burst in different physiological media.
Keywords: Nanoparticles; Chitosan; Humans; povrchové vlastnosti; povrchově aktivní látky; Polyesters; Temperature; Surface-Active Agents; Lactic Acid; doxorubicin; teplota; Doxorubicin; Polylactide; Drug Delivery Systems; lidé; molekulární struktura; velikost částic; dakarbazin; Molecular Structure; polymery; 2-hydroxypropanoic acid (PubChem CID:612); Polymers; polyestery; Dacarbazine; Male; Temozolomide (PubChem CID:5394); lékové transportní systémy; nanočástice; Temozolomide; Drug delivery System; temozolomid; Chitosan (PubChem CID:71853); mužské pohlaví; chitosan; kyselina mléčná; Particle Size; Surface Properties; Doxorubicin (PubChem CID:31703)